Potensi Pura Desa Pura Puseh Desa Pakraman Batuan Sebagai Daya Tarik Wisata Di Kabupaten Gianyar - Dwi Reni Mahaputri; I Putu Anom (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Potency of a tourist attraction is the most important things that can be pulled tourist visits. This research attempts to examine the potencies anything which is found in Desa Temple Puseh Temple Batuan Village. This research is expected could be referred to in the management of Desa Temple Puseh Temple Batuan Village can increase the time and the number of tourist visits. Informants in research were calculated by using the method the base informant and key informants. Technique data collection uses the observation, interview, and study literature. Data analysis technique used descriptive qualitative model Miles and Huberman. The results of the research indicate that Desa Temple Puseh Temple Batuan Village as tourist attraction in Gianyar Regency not only have potencies of temple architecture and relic historical on occasion of the temple existence as one of cultural heritage, but also the tample have uniqueness potencie, such as art like dance, painting, and than a religious ceremony implemented in the temple area can be packaged to be a tourist product that can increase tourist visit durasion and can be beneficial for the Batuan Village community. Keywords:Potencies, Tourism Attraction, Desa Temple Puseh Temple Batuan Village